Understanding the Role of social media in Shaping Millennial Generation Legal Awareness in the Digital Age - Tamaulina Br Sembiring; Irma Rachmawati Maruf; Suryadi Suryadi; Suyani Suyani; Moh Amin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to gain an in-depth understanding and knowledge of the role of social media in shaping and preparing the compliant and law-aware millennial generation in an era of all-digital technology. The author believes that the existence of social media is phenomenal and that it has benefited many parties, including the millennial generation, to learn legal lessons and habits. For this reason, we searched data from several literature sources; then, we entered the stage of analyzing the data to understand and answer the issues and problems of this study with high validity. The review process involves a coding system and a comprehensive data evaluation to obtain relevant findings to answer the problem. Based on our in-depth study and discussion, we have found that social media plays a vital role in providing information, educational inspiration, and motivation for the millennial generation to become aware, obedient, and law-abiding people in Indonesia. Therefore, the government or any party committed to making the law aware should make social media one of the most innovative means of shaping and transforming the millennial generation to become a generation consisting mainly of law-conscious people. It is hoped that the results of this study will serve as a guide for future studies.